2020
DOI: 10.14356/kona.2020019
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Sedimentation of Aqueous Suspension of Na-montmorillonite in the Very Dilute Domain

Abstract: The scheme of DLVO theory and the concept of fractal structure of flocs applied to the suspension of montmorillonite have revealed out the unique nature of this clay dispersion. In this context, two major regimes are recognized. The first is the electrostatically dispersed regime. And the second is the coagulated regime. In the former, the formation of a diffusive electric double layer (EDL) characterized by reciprocal Debye length measured from the surface of the particle is distinctively important. Intrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 95 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…As desired, the majority of the grains (>87%) has a diameter smaller than 2 µm and only 5% of the grains are larger than 20 µm (Dohrmann, 2020). For our analysis, we will use clay suspensions with a concentration of 4, 6, and 8 ppt, respectively (ppt in parts per thousand as the mass fraction) which corresponds to the semidilute regime (Zhu et al, 2018;Adachi et al, 2020;Ghazali et al, 2020). After the preparation of the suspensions, the samples were stored in a dark environment for a minimum of 7 days to establish an equilibrium between the exchangeable ions and the ions in the salt water solution.…”
Section: Fluid and Clay Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As desired, the majority of the grains (>87%) has a diameter smaller than 2 µm and only 5% of the grains are larger than 20 µm (Dohrmann, 2020). For our analysis, we will use clay suspensions with a concentration of 4, 6, and 8 ppt, respectively (ppt in parts per thousand as the mass fraction) which corresponds to the semidilute regime (Zhu et al, 2018;Adachi et al, 2020;Ghazali et al, 2020). After the preparation of the suspensions, the samples were stored in a dark environment for a minimum of 7 days to establish an equilibrium between the exchangeable ions and the ions in the salt water solution.…”
Section: Fluid and Clay Propertiesmentioning
confidence: 99%
“…If clay minerals are dispersed to their primary clay platelets smaller than 1 μm, suspended particles of this size can form ideal sols, where the weight of the particles is balanced by Brownian motion and particles do not settle out over time (Partheniades, 2009;Berg, 2010). There has been evidence that such a state can be obtained in the laboratory if clay particles are dispersed in de-ionized water and flocculation is triggered at a critical salt concentration (e.g., Seiphoori et al, 2021;Mietta et al, 2009;Mehta, 2014;Sutherland et al, 2015;Adachi et al, 2020;Ghazali et al, 2020). However, this critical salt concentration to trigger coagulation, often times referred to as the Critical Coagulation Concentration (CCC, van Olphen, 1977), has not been reported for natural aquatic environments in such a consistent manner (e.g., Gibbs et al, 1989;Droppo and Ongley, 1994;Thill et al, 2001;Kumar et al, 2010;Mikeš and Manning, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When shear forces are applied to surface-charged particles, the electric double layers surrounding the particles are deformed, which increases η and [η] of the particle dispersions 27) . This is termed as a primary electroviscous effect.…”
Section: Intrinsic Viscosity Of Nanocellulose Dispersionsmentioning
confidence: 99%
“…When metal cations are dissolved in water, they neutralize the negative charges on the surface of clay particles and change the interactions between clay particles, such as Coulomb repulsion, double-layer repulsion, and Johannes D. van der Waals attraction. Adachi et al [ 1 ] applied the scheme of DLOV theory (named after Derjaguin, Landau, Verwey, and Overbeek and is the quantitative explanation of charged colloid stability) and the concept of fractal structure of flocs to the suspension of montmorillonite; they put forward that soil particles are always present in the electrostatically dispersed regime and the coagulated regime, and the study revealed the unique nature of this clay dispersion. Additionally, because of the nature of the ionization effect in the aftermath of organic matter in water, macromolecular organic matter, through hydrogen bonding, adsorbs to the surface of the clay particles, prompting clay particle flocculation, affecting the precipitation process of clay particles and the formation of a different microstructure [ 2 ], resulting in the physical and mechanical properties of the soil being significantly different.…”
Section: Introductionmentioning
confidence: 99%